The Effect of Corporate Characteristics and Corporate Governance to Sustainability Report Disclosure in Lq45 Company Listed on Indonesia Stock Exchange Period 2012-2016 - Meinarsih, Triana (International Journal of Psychosocial Rehabilitation, 2020)
This research is intended to analyze the effect of profitability, liquidity, leverage, Firm size, audit committee, board of director, and governance committee to sustainability report disclosure in lq45 company listed on Indonesia stock exchange period 2012-2016”, using path analysis method in a quantitative approach. The population was 45 companies included in the LQ 45 and sample in this study was 17 companies. This research is based on purposive sampling method. The hypothesis test in this research used logistic regression analysis, using the program Eviews 8.00. The results of research showed that partially the liquidity, audit committee, and governance committee have effect and significant to sustainability report disclosure. While variable profitability, leverage, firm size and board of director have not significantly effect to sustainability report disclosure.